2009
DOI: 10.1007/s00445-009-0289-3
|View full text |Cite
|
Sign up to set email alerts
|

Analogue models of the effect of long-term basement fault movement on volcanic edifices

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 51 publications
1
14
0
1
Order By: Relevance
“…1D), interpreted as the delimiting landslide detachment (Gertisser et al, 2012), has a trend that is NNW-SSE on the SE sector of the volcano, curving to a NNW-SSE trend on the NW sector of the volcano edifice. Such curving fault trends on volcanoes have been described by crustal faults that are upwardly propagating into a volcano edifice (Wooller et al, 2009). In our conceptual understanding, Merapi is underlain by a structurally weak zone oriented NNW-SSE, which has influenced growth of adjacent volcanoes, development of valleys and flank instabilities and which has now also influenced the development of a fracture splitting the lava dome in two parts (Fig.…”
Section: The Nnw-sse Trendmentioning
confidence: 98%
“…1D), interpreted as the delimiting landslide detachment (Gertisser et al, 2012), has a trend that is NNW-SSE on the SE sector of the volcano, curving to a NNW-SSE trend on the NW sector of the volcano edifice. Such curving fault trends on volcanoes have been described by crustal faults that are upwardly propagating into a volcano edifice (Wooller et al, 2009). In our conceptual understanding, Merapi is underlain by a structurally weak zone oriented NNW-SSE, which has influenced growth of adjacent volcanoes, development of valleys and flank instabilities and which has now also influenced the development of a fracture splitting the lava dome in two parts (Fig.…”
Section: The Nnw-sse Trendmentioning
confidence: 98%
“…Also, Rungwe is likely to be undercut by a NW-SE fault (NgoziRungwe Line) presumably with the same movement as the Mbaka Fault (normal or oblique/strike-slip). It has been found through analogue modelling (Wooller et al, 2009) that such systems (volcanoes with undercutting normal faults or normal/strike-slip faults passing near the foot) are unstable with strike-slip faulting and can promote flank collapse and the generation of debris avalanches in a direction sub-orthogonal to the major faulting. The work from two field seasons by two of us (KF, GGJE) combined with RS analysis, shows the Rungwe summit crater ( Fig.…”
Section: Significance Of Tectonic Control For Volcanic Activity and Fmentioning
confidence: 99%
“…Van Wyk de Vries and Merle (1998) and Lagmay et al (2000) studied the effects of transcurrent faulting on the volcanoes by performing analogue model experiments that demonstrated that edifices instability can be triggered by an underlying active strike-slip fault. The instability and consequent landslides were oriented approximately 10°-30°f rom the trend of the main strike-slip fault (Lagmay et al, 2000;Wooller et al, 2009;Norini and Lagmay, 2005;Lagmay and Valdivia, 2006;Norini et al, 2008).…”
Section: Role Of Regional Tectonicsmentioning
confidence: 99%